A Biometric Assessment of a Combined Topical Levofloxacin, Retinol, Cloxacillin and Ascorbic acid Against Facial Acne - Naser A Naser1, Hussein Abdulkadhim A2, Sahar A. Alhar3, Karrar K. Alhaidary4, Rana Talib Al-Nafakh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Acne vulgaris is a common pilosebaceous lesion affects skin over the face and upper chest. It has about 14 million incidence rate that cost 100 for each case. In this study, biometric outcomes of the combined retinol, levofloxacin, cloxacillin, ascorbic acid and the hydrocarbon base vehicle on different types of acne lesions in human were investigated. Twenty one person were included in two groups; test (N =10) and control (N = 11) with follow up of objective software based biometric analysis parameters including: keratolysis induction, redness reduction and healing of infected lesion. The test formula revealed a significant keratolysis induction as compared with control. Eight out of 10 individuals with the test formula had keratolysis in comparison with 2 out of 11 had no keratolysis in controlled group, P-Value = 0.005. Similar effects were obtained in redness reduction (redness reduction ratio induced with test formula = 2.5 with confidence interval CI over 0.95) and impetiginization healing at P < 0.05. From the overall results, the combined retinol, levofloxacin, cloxacillin, ascorbic acid and the hydrocarbon base vehicle showed significant improvement in biometric outcomes of facial acne lesions.